2006
DOI: 10.1128/aem.01052-06
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Growth of Escherichia coli with 2,4,6-Trinitrotoluene (TNT) as the Sole Nitrogen Source and Evidence of TNT Denitration by Whole Cells and Cell-Free Extracts

Abstract: Escherichia coli grew aerobically with 2,4,6-trinitrotoluene (TNT) as sole nitrogen source and caused TNT's partial denitration. This reaction was enhanced in nongrowing cell suspensions with 0.516 mol nitrite released per mol TNT. Cell extracts denitrated TNT in the presence of NAD(P)H. Isomers of amino-dimethyl-tetranitrobiphenyl were detected and confirmed with U-15 N-labeled TNT.2,4,6-Trinitrotoluene (TNT) is recalcitrant to microbial degradation. Denitration (defined as the release of nitrite) is a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 23 publications
(25 reference statements)
2
35
1
Order By: Relevance
“…However, these amino derivatives tend to accumulate in the environment and are not degraded further. More interesting, a few bacteria have been reported to denitrate TNT [10,40] with the production of metabolites known to be easily mineralized [34]. Among those, a new Pseudomonas aeruginosa strain was recently isolated by Eyers et al from the soil KX1 (manuscript submitted).…”
Section: Total and Culturable Bacterial Diversity In Tnt-contaminatedmentioning
confidence: 95%
See 1 more Smart Citation
“…However, these amino derivatives tend to accumulate in the environment and are not degraded further. More interesting, a few bacteria have been reported to denitrate TNT [10,40] with the production of metabolites known to be easily mineralized [34]. Among those, a new Pseudomonas aeruginosa strain was recently isolated by Eyers et al from the soil KX1 (manuscript submitted).…”
Section: Total and Culturable Bacterial Diversity In Tnt-contaminatedmentioning
confidence: 95%
“…OK-5 (Xanthomonadaceae), which is able to resist TNT-mediated stress by producing stress shock proteins [19] and to grow on TNT as sole nitrogen source [35], no other member of the families Comamonadaceae, Xanthomonadaceae and Caulobacteraceae has been reported so far to metabolize TNT. Indeed, bacteria known to degrade TNT aerobically and/or anaerobically belong to Pseudomonadaceae, Enterobacteriaceae, Mycobacteriaceae, Nocardiaceae, Desulfovibrionaceae, Clostridiaceae and Bacillaceae [36,40,41]. The presence of species belonging to Comamonadaceae, Xanthomonadaceae and Caulobacteraceae in soils with very high concentrations of TNT, where pore water is very probably saturated with TNT [44], suggests that those new species are at least tolerant to the presence of TNT.…”
Section: Total and Culturable Bacterial Diversity In Tnt-contaminatedmentioning
confidence: 98%
“…In the course of our attempts to clone and identify other genes of Pseudomonas JLR11 encoding proteins involved in TNT metabolism, we designed a cloning strategy using Escherichia coli as a host strain. The series of controls indicated that E. coli was able to use TNT as the sole nitrogen source, thereby confirming recent findings (Stenuit et al ., 2006). In fact, it has long been known that E. coli cells growing aerobically or anaerobically are able to reduce up to two of the nitro groups of TNT to yield 2,4‐diamino‐6‐nitrotoluene (McCormick et al ., 1976; Ederer et al ., 1997; Fuller and Manning, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, even negative results of screening a metagenomic library because of an ill-adapted host organism can be valuable, as illustrated by our recent discovery of strong TNT denitration capacity in Escherichia coli, the host par excellence, while screening for TNT denitration activity a metagenomic library which we established using DNA from soil historically contaminated with this recalcitrant explosive (Stenuit et al 2006). In this same context, valuable insights about shifts in microbial community structure as a result of TNT contamination were recently obtained by us using microarray probing as pointed out above and fingerprinting techniques (George et al 2008).…”
Section: Application Of Molecular Techniques In Contaminated Sites Fomentioning
confidence: 97%